Distribuição da mastofauna de médio e grande porte em um mosaico florestal - Mello, Andrei (Universidade do Vale do Rio do Sinos, 2005)
Medium and large mammals occur in all world ecosystems. Their ecological role is very important, since they contribute for the maintenance of the equilibrium of their communities. The mammal diversity in the Atlantic forest and, specifically, in the Araucaria Forest (FO) of southern Brazil is very high. However, mainly due to the high value of Araucaria angustifolia (the dominant species of the FO) as timber, this forest formation has been intensely fragmented, with large areas being replaced by arboreal plantations of both introduced and native species. In this study we investigated how the medium and large-sized mammalian fauna uses a forest mosaic composed of patches of MOF and plantations of Pinus spp., Eucalyptus sp., and also A. angustifolia. For data collection I used trapping grids of sand track stations placed in all habitats (9 stations per grid, total area of 0.64 ha), with three grids (replicates) for each habitat. In this stations I used three bait types: banana, bacon and Pipdog. I es
Keywords: Floresta com araucária; Mamíferos; Mosaico florestal; Uso de hábitat; Araucaria Forest; Forest mosaic; Habitat utilization; Mammals; Ciências Biológicas